Transition Pathways Towards Sustainability in Agriculture: Case Studies From Europe 2014
DOI: 10.1079/9781780642192.0157
|View full text |Cite
|
Sign up to set email alerts
|

Local quality and certification schemes as new forms of governance in sustainability transitions.

Abstract: In this chapter, local certification schemes are assessed in relation to the role that new forms of governance can play in facilitating sustainability transitions. The chapter focuses, particularly, on the interactions between new forms of horizontal governance emerging in local quality and certification 'niches', and the vertical forms of governance characterizing the agriculture and tourism or environmental protection regimes in which these niches develop. Three case studies situated in Bulgaria, the Czech R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The authors also claim that it is part of the development of new models of both production and consumption, which simultaneously contribute to the creation and development of alternative food distribution channels and new models for rural development. Moreover, another study [27] found an important issue related to the possibilities of new government structures emerging based on local actors networking to utilize the specific territorial characteristics and production of traditional food. It is fact that, in the cases of new initiatives, existing governance structures could hamper their development simply because they are not part of the mainstream.…”
Section: Literature Review 21 the Importance Of Local And Regional Products For The Economy And Environment On Micro And Macro Scales-litmentioning
confidence: 99%
“…The authors also claim that it is part of the development of new models of both production and consumption, which simultaneously contribute to the creation and development of alternative food distribution channels and new models for rural development. Moreover, another study [27] found an important issue related to the possibilities of new government structures emerging based on local actors networking to utilize the specific territorial characteristics and production of traditional food. It is fact that, in the cases of new initiatives, existing governance structures could hamper their development simply because they are not part of the mainstream.…”
Section: Literature Review 21 the Importance Of Local And Regional Products For The Economy And Environment On Micro And Macro Scales-litmentioning
confidence: 99%